2022
DOI: 10.7717/peerj.13586
|View full text |Cite
|
Sign up to set email alerts
|

Assessing availability of European plant protection product data: an example evaluating basic area treated

Abstract: Besides the benefits of plant protection products (PPPs) for agricultural production, there is an increasing acknowledgement of the associated potential environmental risks. Here, we examine the feasibility of summarizing the extent of PPP usage at the country level, using Ireland as a case study, as well as at the European level. We used the area over which PPPs are applied (basic area) as an example variable that is relevant to initially assess the geographic extent of environmental risk. In Irish agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Although our knowledge of fungicides and the potential implications of exposure to fungicides for bees is increasing, the fungicide prothioconazole is greatly understudied ( Cullen et al, 2019 ) and as such needs more research attention. This is particularly important as it is widely used ( López-Ballesteros, et al, 2022 ) and residues can be found in nectar and pollen ( Wallner, 2009 ; Roszko et al, 2016 ; Bokšová et al, 2021 ), thereby resulting in oral exposure of bees. We found there was consistently no impairment in learning ability caused by prothioconazole across experiments two and three, which provides strong evidence that prothioconazole may not cause reductions in olfactory learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our knowledge of fungicides and the potential implications of exposure to fungicides for bees is increasing, the fungicide prothioconazole is greatly understudied ( Cullen et al, 2019 ) and as such needs more research attention. This is particularly important as it is widely used ( López-Ballesteros, et al, 2022 ) and residues can be found in nectar and pollen ( Wallner, 2009 ; Roszko et al, 2016 ; Bokšová et al, 2021 ), thereby resulting in oral exposure of bees. We found there was consistently no impairment in learning ability caused by prothioconazole across experiments two and three, which provides strong evidence that prothioconazole may not cause reductions in olfactory learning.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to investigate the impacts of the herbicide glyphosate and the fungicide prothioconazole on bees, as the most widely used herbicide and fungicide compounds in Ireland ( López-Ballesteros, et al, 2022 ). Glyphosate is also the most applied herbicide in the world (in terms of kg used; Benbrook, 2016 ), and is a broad-spectrum and non-selective herbicide employed for a variety of uses in agriculture, but also heavily used in domestic and amenity settings ( Duke and Powles, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the pyrethroids and organophosphates are projected to represent the highest ranked compounds with purely insecticidal properties in terms of application rate in the world (Maggi et al, 2019), and in some countries are already the number one most widely applied in terms of basic area (e.g. the pyrethroids in Ireland, López-Ballesteros et al, 2022;and the UK, FERA, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the pyrethroids and organophosphates are projected to represent the highest ranked compounds with purely insecticidal properties in terms of application rate in the world (Maggi et al, 2019), and in some countries are already the number one most widely applied in terms of basic area (e.g. the pyrethroids in Ireland, López‐Ballesteros et al, 2022; and the UK, FERA, 2020). To date, beyond the standard lower tier LD50 ecotoxicological tests used for honeybees in pesticide registration, we know little about how these non‐neonicotinoid classes of insecticides may affect bees more generally (but see; Baron et al, 2014; Gill et al, 2012) and in particular whether they have any sublethal impacts.…”
Section: Introductionmentioning
confidence: 99%